PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA PADA MURID KELAS V SD NEGERI NO.56 PA’LILANG - St. Maghvira; Muhajir; Try Gustaf Said (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) model on the learning outcomes of Pancasila Education among fifth-grade students of SD Negeri No. 56 Pa’lilang. The type of research used is quantitative research with a pre-experimental design using the One Group Pretest–Posttest Design. The research sample consisted of 14 fifth-grade students. The data collection techniques were conducted through learning outcome tests, namely pretest and posttest, as well as observations of students' activities during the learning process. The obtained data were analyzed using a normality test and hypothesis testing with the Paired Sample t-test using the SPSS program. The results of the study indicate that the implementation of the Problem Based Learning (PBL) model has a significant effect on students’ learning outcomes. This is shown by the increase in the students' average score from 62.14 in the pretest to 87.14 in the posttest, as well as the increase in learning mastery from 43% to 100%. The results of the Paired Sample t-test showed a significance value of 0.000 < 0.05 with |t count| = 14.381, which is greater than t table = 2.160, therefore H₀ is rejected and H₁ is accepted. Thus, it can be concluded that the Problem Based Learning (PBL) model has a significant effect on the learning outcomes of Pancasila Education among fifth-grade students of SD Negeri No. 56 Pa’lilang.